Composite repairing agent of charcoal-loaded pyrrhotite as well as preparation method and application of composite repairing agent
By uniformly dispersing pyrite on biochar and combining persulfate to form an advanced oxidation system, the problem of difficulty in removing SMX pollution in groundwater in the prior art is solved, and efficient and economical pollution repair effect is achieved.
Patent Information
- Application Number
- CN202510150717.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to effectively remove sulfamethoxazole (SMX) pollution in groundwater, and traditional restoration technology has problems such as inactivation of plate bonds of industrial energy materials, system blockage, and secondary pollution caused by chemical oxidation.
Through a simple one-pot solvent-thermal synthesis method, a composite repair agent of biochar loaded pyrite (Fe7S8@BC) was prepared, so that Fe7S8 was evenly dispersed and loaded on the surface of biochar, and combined with persulfate to form an advanced oxidation system, which was used for SMX pollution repair in groundwater.
It achieves efficient oxidation and degradation of SMX, prevents pollution from spreading outward, and has a simple process and low cost, making it suitable for large-scale industrial production.
Smart Images

Figure CN119869454A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of groundwater restoration, and in particular to a composite restoration agent of biochar loaded with pyrrhotite, and a preparation method and application thereof. Background Art
[0002] Due to their widespread use, antibiotics persist in the environment through biotransformation and accumulation, leading to an increasingly prominent problem of drug resistance. The presence of antibiotics may inhibit or kill sensitive microorganisms in the environment, leading to an imbalance in the ecosystem. Secondly, although the concentration of antibiotics in the environment is low, it is sufficient to exert selection pressure on microorganisms and promote the spread of drug-resistant genes. In addition, antibiotics can accumulate in aquatic organisms, be transmitted through the food chain, and ultimately affect human health. Sulfadimethoxazole (SMX) is a widely used synthetic sulfonamide antibiotic that enters the soil and groundwater in the form of a precursor drug after being metabolized in humans and animals, resulting in a large amount of such substances in the groundwater environment. Due to its high chemical stability, strong bacterial resistance, potential carcinogenicity and significant ecotoxicity, SMX is difficult to degrade in the environment, leading to the emergence of many drug-resistant pathogens and even superbugs, posing a major threat to ecosystem security and seriously endangering human health.
[0003] At present, the commonly used remediation technologies for SMX groundwater contamination include permeable reaction wall technology, chemical oxidation technology and biological remediation technology. However, during the long-term use of traditional PRBs, problems such as hardening and inactivation of engineering materials, system blockage and difficulty in replacing fillers will occur; chemical oxidation technology requires the use of a large amount of chemical agents, which will destroy the groundwater redox environment and the structure of environmental microbial communities, and easily cause secondary pollution; biological degradation or absorption and transformation of organic pollutants usually takes a long time and the efficiency is greatly affected by environmental factors. Therefore, it is urgent to develop a functional material and remediation system that is efficient for the remediation of SMX contaminated groundwater.
[0004] The prior art discloses a method for repairing contaminated soil and recovering hexavalent chromium (Cr(VI)) in situ using renewable magnetic mineral composite materials. The method adds a composite material of magnetite and pyrrhotite to Cr(VI) contaminated soil and mixes it thoroughly. After a certain period of repair, the Cr(VI) content in the soil can be effectively reduced, and the Cr(VI) content in the obtained soil is lower than the national risk control standard. Also disclosed is an artificial wetland system and method for enhancing the removal of divalent mercury (Hg(II)) in water. The invention introduces pyrrhotite as a mixed matrix filler for artificial wetlands, enhances the reduction activity of the wetland matrix ZVI, and improves the removal efficiency of Hg(II). The artificial wetland system in the invention has a high removal efficiency of Hg(II), a strong comprehensive ability to purify water, and the electron transfer between microorganisms, Fe, S and Hg(II) pollutants will be promoted. Also disclosed is a composite flocculant for treating low-temperature and low-turbidity water and a preparation method. The composite flocculant prepared in the invention is composed of nano-modified natural mordenite, water glass, nano-natural pyrrhotite and nano-ferroferric oxide, which is suitable for lateral purification of polluted river water, has the characteristics of fast flocculation and sedimentation time, high purification efficiency, and can achieve a removal rate of ammonia nitrogen of more than 30%. It can be added to the influent of the secondary sedimentation tank to effectively improve the sedimentation performance of sludge. A method for treating Cr(VI) wastewater based on pyrrhotite biochar loaded with acidophilic bacteria biofilm is also disclosed, which has the advantages of low cost, mild reaction, simple process and high chromium removal rate, and can be applied to the treatment of Cr(VI)-containing wastewater in electroplating plants, smelters, electronics plants, etc.
[0005] Although pyrrhotite is used for soil and contaminated water remediation in the prior art, it only focuses on the remediation of non-organic pollutants (such as Cr(VI), Hg(II) and ammonia nitrogen, etc.), and does not fully utilize the activation performance of pyrrhotite and the contaminated groundwater environment medium. The application potential of pyrrhotite in the field of groundwater antibiotic contamination remediation has not been fully explored. Therefore, it is very necessary to develop a preparation and application method of a biochar-loaded pyrrhotite composite remediation agent. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a biochar-loaded pyrrhotite composite repair agent and a preparation method and application thereof. The method uses a simple one-pot solvent thermal synthesis method to uniformly disperse Fe7S8 on the BC surface with a unique pore structure (agglomeration is effectively alleviated).
[0007] To this end, the present invention provides the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a composite repair agent of biochar-loaded pyrrhotite in an optional embodiment, comprising the following steps:
[0009] S1: After crushing, pyrolyzing, cooling, grinding and screening the carbon-based biomass, BC materials are obtained;
[0010] S2: Dissolve the iron salt, ferrous salt, sulfur source and BC material, stir evenly, heat, cool to room temperature, wash and dry to obtain a composite repair agent;
[0011] In the composite repair agent, the molar ratio of Fe7S8 to BC is 1:1-5.
[0012] In the biochar-loaded pyrrhotite composite repair agent of the present invention, biochar refers to BC and pyrrhotite refers to Fe7S8.
[0013] Preferably, in step S1, the pyrolysis method includes the following steps: heating the crushed carbon-based biomass to 100°C at a rate of 5°C / min at room temperature, maintaining for 1 hour, and then heating to 500°C at a rate of 10°C / min, and maintaining for 2 hours; and / or, the carbon-based biomass is selected from one or more of peanut shells, corn stalks or cow dung; and / or, when performing pyrolysis, it is carried out under an atmosphere of protective gas, and the protective gas includes one or more of nitrogen, helium or neon.
[0014] Preferably, in step S2, the dissolving solvent is one of ethylene glycol and water; and / or the heating temperature is 220-260°C and the time is 10-14h; and / or the washing solution is pure water and ethanol, and the number of times is at least 3 times; and / or the drying temperature is 50-70°C and the time is 5-7h; and / or the iron salt is selected from one or more of ferric chloride, ferric nitrate or ferrous sulfate; and / or the ferrous salt is selected from one or more of ferrous sulfate, ferrous chloride or ferrous nitrate; and / or the sulfur source is selected from one or more of sodium sulfide, thiourea, thioacetamide or elemental sulfur.
[0015] In a second aspect, the present invention provides, in an optional embodiment, a composite repair agent of biochar loaded with pyrrhotite, which is prepared by the above-mentioned preparation.
[0016] In a third aspect, the present invention provides a method for remediating antibiotic contamination in groundwater in an optional embodiment, comprising the following steps:
[0017] The composite remediation agent of biochar loaded with pyrrhotite and persulfate are added to the contaminated groundwater containing antibiotics, and the pH value is adjusted to 2-6 and then shaken;
[0018] Wherein, the molar ratio of the composite repair agent of biochar loaded with pyrrhotite to persulfate is 1:3.264-13.056.
[0019] Preferably, before adjusting the pH value, the contaminated groundwater contains 1.5-2.5 mmol / L of a biochar-loaded pyrrhotite composite repair agent, 0.3-0.5 g / L of persulfate and 8-12 mg / L of an antibiotic; and / or, the persulfate is selected from one or more of sodium persulfate, potassium persulfate or potassium hydrogen persulfate; and / or, the antibiotic is selected from one or more of sulfamethoxazole, ofloxacin or tetracycline.
[0020] In a fourth aspect, the present invention provides, in an optional embodiment, a dynamic repair column, comprising a water inlet, a water outlet, and a chromatography column;
[0021] The chromatography column is provided with a first filling area, a second filling area and a third filling area, the first filling area, the second filling area and the third filling area are separated by a nylon mesh, the first filling area and the third filling area are filled with glass beads, and the second filling area is filled with a mixture of the composite repair agent of biochar loaded with pyrrhotite and quartz sand;
[0022] The water inlet is arranged at one end of the chromatography column and connected to a peristaltic pump, and is used to input contaminated groundwater into the dynamic remediation column;
[0023] The water outlet is arranged at the other end of the chromatography column;
[0024] Wherein, in the second filling area, the mass ratio of the biochar-loaded pyrrhotite composite repair agent to quartz sand is 0.02-0.06:15.
[0025] Preferably, the contaminated groundwater contains 8-12 mg / L of antibiotics and 1.8-2.2 mmol / L of persulfate.
[0026] In a fifth aspect, the present invention provides, in an optional embodiment, an application of the above-mentioned biochar-loaded pyrrhotite composite repair agent in repairing antibiotic contamination in groundwater.
[0027] Preferably, the application comprises the following steps: injecting the composite repair agent of the biochar loaded with pyrrhotite into different soil layers through an injection well, continuously injecting the composite repair agent at adjacent positions in the region to form two rows of parallel reagent layers, and constructing a reaction zone of the composite repair agent;
[0028] Water and persulfate are continuously circulated and injected into the soil layer of the underground contaminated area through injection wells to form a composite remediation agent / persulfate advanced oxidation system of biochar-loaded pyrrhotite, which continuously releases strong oxidants and efficiently oxidizes and degrades antibiotics in the soil and groundwater;
[0029] The water after oxidation degradation is extracted through extraction wells, and the water that meets the discharge standards is then introduced into the injection wells on both sides to form a hydraulic cycle.
[0030] Compared with the prior art, the present invention has one of the following beneficial effects:
[0031] 1. The method provided by the present invention uses a simple one-pot solvent thermal synthesis method to uniformly disperse Fe7S8 on the BC surface with a unique pore structure (agglomeration is effectively alleviated).
[0032] 2. The present invention has the advantages of cheap raw materials and simple synthesis, and is expected to be used for large-scale industrial production of composite repair agents.
[0033] 3. The composite remediation agent of biochar-loaded pyrrhotite provided by the present invention can prevent antibiotic pollution from spreading outwards on the one hand; on the other hand, the antibiotics are concentrated near the reaction zone and are more easily oxidized and degraded. Ultimately, the purpose of applying the biochar-loaded pyrrhotite / persulfate system to the efficient remediation of antibiotic groundwater pollution is achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 This is a scanning electron microscope result of the composite repair agent of biochar loaded with pyrrhotite prepared in Example 1 of the present invention;
[0036] Figure 2 This is an experimental diagram showing the remediation performance of the remediation agent of the present invention on antibiotics in contaminated groundwater under different conditions;
[0037] Figure 3 It is a schematic diagram of the structure of the dynamic repair column of Example 4 of the present invention and Comparative Example 3;
[0038] Figure 4 The results of the experiment on the repair performance of the dynamic repair column of the composite repair agent containing different dosages of biochar loaded with pyrrhotite in Example 4 of the present invention;
[0039] Figure 5 This is a schematic diagram of the specific application of the composite repair agent of biochar loaded with pyrrhotite in the repair of antibiotic contamination in groundwater. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0041] Example 1
[0042] This embodiment provides a method for preparing a composite repair agent of biochar loaded with pyrrhotite, comprising the following steps:
[0043] S1: Peanut shells were used as precursors. They were softened and dispersed by preliminary grinding. The peanut shells were evenly loaded into a closed quartz tube and pyrolyzed in a nitrogen (N2) atmosphere tube furnace. The pyrolysis program was set as follows: the heating rate was set to 5°C / min, and the temperature was raised from 0°C to 100°C and maintained for 1h. Subsequently, the heating rate was increased to 10°C / min, and the temperature was continuously raised from 100°C to 500°C and maintained for 2h. After the pyrolysis program was completed, the tube furnace was naturally cooled to room temperature, and then ground and sieved (200 mesh screen) to finally obtain BC material.
[0044] S2: 0.27g FeCl3·6H2O, 0.70g FeSO4·7H2O, 1.2g Na2S·9H2O and 0.138g BC materials were dissolved in ethylene glycol (60mL) respectively, and stirred for 20min to ensure that the precursors were evenly mixed; the rotor was removed by a magnet, the precursor was transferred to a 100mL polytetrafluoroethylene liner, and placed in a stainless steel high-pressure reactor, and heated at 240°C for 12h; after the heating, it was cooled to room temperature, the materials in the liner were collected, and washed three times with ultrapure water and ethanol respectively to remove the existing impurities; the washed materials were vacuum dried at 60°C for 6h to remove residual moisture and ethanol, and a biochar-loaded pyrrhotite composite repair agent (Fe7S8@BC) was obtained, which was stored under N2 conditions for standby use. In the Fe7S8@BC composite repair agent of this embodiment, the molar ratio of Fe7S8 to BC was 1:1. The Fe7S8@BC composite repair agent prepared in Example 1 was subjected to scanning electron microscopy. Figure 1 .
[0045] Example 2
[0046] This embodiment provides a method for preparing a composite repair agent of biochar loaded with pyrrhotite, comprising the following steps:
[0047] S1: Peanut shells were used as precursors. They were softened and dispersed by preliminary grinding. The peanut shells were evenly loaded into a closed quartz tube and pyrolyzed in a nitrogen atmosphere tube furnace. The pyrolysis program was set as follows: the heating rate was set to 5°C / min, and the temperature was raised from 0°C to 100°C and maintained for 1h. Subsequently, the heating rate was increased to 10°C / min, and the temperature was continuously raised from 100°C to 500°C and maintained for 2h. After the pyrolysis program was completed, the tube furnace was naturally cooled to room temperature, and then ground and sieved (200 mesh screen) to finally obtain BC material.
[0048] S2: 0.27g FeCl3·6H2O, 0.70g FeSO4·7H2O, 1.2g Na2S·9H2O and 0.414g BC materials were dissolved in ethylene glycol (60mL) respectively, and stirred for 20min to ensure that the precursors were evenly mixed; the rotor was removed by a magnet, the precursor was transferred to a 100mL polytetrafluoroethylene liner, and placed in a stainless steel high-pressure reactor, and heated at 240°C for 12h; after the heating, it was cooled to room temperature, the materials in the liner were collected, and washed three times with ultrapure water and ethanol respectively to remove the existing impurities; the washed materials were vacuum dried at 60°C for 6h to remove residual moisture and ethanol, and a biochar-loaded pyrrhotite composite repair agent (Fe7S8@BC) was obtained, which was stored under N2 conditions for standby use. In the Fe7S8@BC composite repair agent of this embodiment, the molar ratio of Fe7S8 to BC was 1:3.
[0049] Example 3
[0050] This embodiment provides a method for preparing a composite repair agent of biochar loaded with pyrrhotite, comprising the following steps:
[0051] S1: Peanut shells were used as precursors. They were softened and dispersed by preliminary grinding. The peanut shells were evenly loaded into a closed quartz tube and pyrolyzed in a nitrogen atmosphere tube furnace. The pyrolysis program was set as follows: the heating rate was set to 5°C / min, and the temperature was raised from 0°C to 100°C and maintained for 1h. Subsequently, the heating rate was increased to 10°C / min, and the temperature was continuously raised from 100°C to 500°C and maintained for 2h. After the pyrolysis program was completed, the tube furnace was naturally cooled to room temperature, and then ground and sieved (200 mesh screen) to finally obtain BC material.
[0052] S2: 0.27g FeCl3·6H2O, 0.70g FeSO4·7H2O, 1.2g Na2S·9H2O and 0.690g BC materials were dissolved in ethylene glycol (60mL) respectively, and stirred for 20min to ensure that the precursors were evenly mixed; the rotor was removed by a magnet, the precursor was transferred to a 100mL polytetrafluoroethylene liner, and placed in a stainless steel high-pressure reactor, and heated at 240°C for 12h; after the heating, it was cooled to room temperature, the materials in the liner were collected, and washed three times with ultrapure water and ethanol respectively to remove the existing impurities; the washed materials were vacuum dried at 60°C for 6h to remove residual moisture and ethanol, and a biochar-loaded pyrrhotite composite repair agent (Fe7S8@BC) was obtained, which was stored under N2 conditions for standby use. In the Fe7S8@BC composite repair agent of this embodiment, the molar ratio of Fe7S8 to BC was 1:5.
[0053] Comparative Example 1
[0054] This comparative example provides a method for preparing a repair agent, comprising the following steps:
[0055] Peanut shell was used as the precursor. It was softened and dispersed through preliminary grinding treatment. The peanut shell was evenly loaded into a closed quartz tube and pyrolyzed in a nitrogen atmosphere tube furnace. The pyrolysis program was set as follows: the heating rate was set to 5℃ / min, and the temperature was increased from 0℃, gradually increased to 100℃ and maintained for 1h. Subsequently, the heating rate was increased to 10℃ / min, and the temperature was continuously increased from 100℃ to 500℃ and maintained for 2h. After the pyrolysis program was completed, the tube furnace was naturally cooled to room temperature, and then ground and sieved (200 mesh sieve) to finally obtain BC material.
[0056] Comparative Example 2
[0057] This comparative example provides a method for preparing a repair agent, comprising the following steps:
[0058] 0.27 g FeCl3·6H2O, 0.70 g FeSO4·7H2O and 1.2 g Na2S·9H2O were dissolved in ethylene glycol (60 mL) respectively and stirred for 20 min to ensure that the precursors were evenly mixed; the rotor was removed by a magnet, and the precursor was transferred to a 100 mL polytetrafluoroethylene liner, and placed in a stainless steel high-pressure reactor and heated at 240°C for 12 h; after the heating was completed, it was cooled to room temperature, the material in the liner was collected, and washed three times with ultrapure water and ethanol respectively to remove the existing impurities; the washed material was vacuum dried at 60°C for 6 h to remove residual moisture and ethanol to obtain Fe7S8.
[0059] Comparative Example 3
[0060] This comparative example provides a method for preparing a composite repair agent, comprising the following steps:
[0061] S1: Peanut shells were used as precursors. They were softened and dispersed by preliminary grinding. The peanut shells were evenly loaded into a closed quartz tube and pyrolyzed in a nitrogen atmosphere tube furnace. The pyrolysis program was set as follows: the heating rate was set to 5°C / min, and the temperature was raised from 0°C to 100°C and maintained for 1h. Subsequently, the heating rate was increased to 10°C / min, and the temperature was continuously raised from 100°C to 500°C and maintained for 2h. After the pyrolysis program was completed, the tube furnace was naturally cooled to room temperature, and then ground and sieved (200 mesh screen) to finally obtain BC material.
[0062] S2: 0.27 g FeCl3·6H2O, 0.70 g FeSO4·7H2O and 1.2 g Na2S·9H2O were dissolved in ethylene glycol (60 mL) respectively and stirred for 20 min to ensure that the precursors were evenly mixed; the rotor was removed by a magnet, the precursor was transferred to a 100 mL polytetrafluoroethylene liner, and placed in a stainless steel high-pressure reactor, and heated at 240°C for 12 h; after heating, it was cooled to room temperature, the material in the liner was collected, and washed three times with ultrapure water and ethanol respectively to remove the impurities; the washed material was vacuum dried at 60°C for 6 h to remove residual water and ethanol to obtain pyrrhotite (Fe7S8);
[0063] S3: Grind 1mmol Fe7S8 and 1mmol BC materials and mix them at high speed to obtain a composite repair agent.
[0064] Comparative Example 4
[0065] This comparative example provides a method for preparing a composite repair agent, comprising the following steps:
[0066] S1: Peanut shells were used as precursors, and were softened and dispersed by preliminary grinding. The peanut shells were evenly loaded into a closed quartz tube and pyrolyzed in a nitrogen atmosphere tube furnace at a temperature of 500°C for 2 hours. After the pyrolysis process was completed, the tube furnace was naturally cooled to room temperature, and then ground and sieved (200 mesh screen) to finally obtain BC material.
[0067] S2: 0.27g FeCl3·6H2O, 0.70g FeSO4·7H2O, 1.2g Na2S·9H2O and 0.138g BC materials were dissolved in ethylene glycol (60mL) respectively, and stirred for 20min to ensure that the precursors were evenly mixed; the rotor was removed by a magnet, and the precursor was transferred to a 100mL polytetrafluoroethylene liner, and placed in a stainless steel high-pressure reactor, and heated at 240°C for 12h; after the heating, it was cooled to room temperature, the materials in the liner were collected, and washed three times with ultrapure water and ethanol respectively to remove the existing impurities; the washed materials were vacuum dried at 60°C for 6h to remove residual moisture and ethanol, and a biochar-loaded pyrrhotite composite repair agent (Fe7S8@BC) was obtained, which was stored under N2 conditions for future use. In the Fe7S8@BC composite repair agent of this comparative example, the molar ratio of Fe7S8 to BC was 1:1.
[0068] Experimental example
[0069] A solution containing 10.0 mg / L of SMX was prepared to simulate SMX-contaminated groundwater, and 50 mL was added to a reaction container, and the pH value of the reaction solution was adjusted to 4.0; 0.02 g of the repair agent prepared in Example 1 and Comparative Examples 3-4 and 0.1 mmol of sodium persulfate were weighed and added to the reaction container, and immediately transferred to a constant temperature oscillator, with the rotation speed and temperature set to 150 r / L and 30°C, respectively; at 60 min, a solution of about 0.5 mL in volume was taken out from the reaction container with a 1 mL syringe, and filtered with a 0.22 μm polytetrafluoroethylene filter membrane, which was recorded as a sample; the samples were detected and analyzed using high performance liquid chromatography (HPLC), and it was found that the removal rate of SMX by the repair agent of Example 1 within 60 min reached 92.5%, while the removal rate of SMX by the repair agent of Comparative Example 3 within 60 min was 86.8%, and the removal rate of SMX by the repair agent of Comparative Example 4 within 60 min was 89.3%.
[0070] A solution containing 10.0 mg / L of SMX was prepared to simulate SMX contaminated groundwater, and 50 mL was added to a reaction vessel, and the pH value of the reaction solution was adjusted to 4.0; 0.02 g of the repair agent prepared in Example 1-3 and Comparative Example 1-2 and 0.1 mmol of sodium persulfate were weighed and added to the reaction vessel, and immediately transferred to a constant temperature oscillator, with the speed and temperature set to 150 r / L and 30° C., respectively; within a fixed time (0 min, 5 min, 10 min, 15 min, 35 min, 45 min, 60 min), a solution with a volume of about 0.5 mL was taken out from the reaction vessel with a 1 mL syringe, and filtered with a 0.22 μm polytetrafluoroethylene filter membrane, recorded as a sample; the above samples were detected and analyzed by high performance liquid chromatography (HPLC) to identify the repair performance of the repair agent prepared in Example 1-3 and Comparative Example 1-2 on SMX, and the results are shown in Figure 2 a.
[0071] Prepare a solution containing 10.0 mg / L of SMX to simulate SMX contaminated groundwater, and take 50 mL to add to the reaction container, adjust the pH value of the reaction solution to 4.0; weigh 0.02 g of the repair agent (Fe7S8@BC 1:1 ) and 0.025mmol sodium persulfate, 0.02g of the repair agent prepared in Example 1 (Fe7S8@BC 1:1 ) and 0.05mmol sodium persulfate, 0.02g of the repair agent prepared in Example 1 (Fe7S8@BC 1:1 ) and 0.1mmol sodium persulfate, 0.02g of the repair agent prepared in Example 1 (Fe7S8@BC 1:1 ) and 0.2mmol sodium persulfate, 0.02g of the repair agent prepared in Example 1 (Fe7S8@BC 1:1 ) and 0.4 mmol sodium persulfate were added to the reaction container, and immediately transferred to a constant temperature oscillator, with the speed and temperature set to 150 r / L and 30° C. respectively; within a fixed time (0 min, 5 min, 10 min, 15 min, 35 min, 45 min, 60 min), a solution of about 0.5 mL in volume was taken out from the reaction container with a 1 mL syringe, and filtered with a 0.22 μm polytetrafluoroethylene filter membrane, which was recorded as a sample; the above samples were detected and analyzed by high performance liquid chromatography (HPLC) to identify the repair performance of the repair agents prepared in Examples 1-3 and Comparative Examples 1-2 on SMX, and the results are shown in Figure 2 c.
[0072] Prepare a solution containing 10.0 mg / L of SMX to simulate SMX contaminated groundwater, and take 50 mL to add to the reaction container, adjust the pH value of the reaction solution to 2.0, 4.0, 7.0, 10.0 and 12.0 respectively; weigh 0.02 g of the repair agent (Fe7S8@BC 1:1 ) and 0.1 mmol sodium persulfate were added to the reaction container, and immediately transferred to a constant temperature oscillator, with the speed and temperature set to 150 r / L and 30° C. respectively; within a fixed time (0 min, 5 min, 10 min, 15 min, 35 min, 45 min, 60 min), a solution of about 0.5 mL in volume was taken out from the reaction container with a 1 mL syringe, and filtered with a 0.22 μm polytetrafluoroethylene filter membrane, which was recorded as a sample; the above samples were detected and analyzed by high performance liquid chromatography (HPLC) to identify the repair performance of the repair agents prepared in Examples 1-3 and Comparative Examples 1-2 on SMX, and the results are shown in Figure 2 d.
[0073] Example 4
[0074] See also Figure 3 In the right figure, this embodiment provides a dynamic repair column, including a water inlet, a water outlet and a chromatography column;
[0075] A first filling area, a second filling area and a third filling area are provided in the chromatography column, and the first filling area, the second filling area and the third filling area are isolated by a nylon mesh, the first filling area and the third filling area are filled with glass beads, and the second filling area is filled with a mixture of the composite repair agent (Fe7S8@BC) of biochar loaded with pyrrhotite prepared in Example 1 and quartz sand;
[0076] The water inlet is arranged at one end of the chromatography column and connected to the peristaltic pump to input the contaminated groundwater into the dynamic remediation column;
[0077] The water outlet is arranged at the other end of the chromatography column;
[0078] Among them, in the second filling area, the mass ratio of the biochar-loaded pyrrhotite composite repair agent and quartz sand is 0.02-0.06:15.
[0079] Contaminated groundwater contains 8-12 mg / L of antibiotics and 1.8-2.2 mmol / L of persulfate.
[0080] The reaction column was placed vertically, and glass beads (1 g, 3.0 mm in diameter), Fe7S8@BC mixed quartz sand (the amount of repair agent was 20 mg, 40 mg and 60 mg, respectively, and the amount of quartz sand was 15 g) and glass beads (1 g, 3.0 mm in diameter) were sequentially loaded into the remediation column. The Fe7S8@BC mixed quartz sand and glass beads were separated by a 100-mesh nylon mesh, and the particle size of the quartz sand was 1-2 mm. Subsequently, the contaminated groundwater storage bottle was connected to the peristaltic pump by a hose, and the water inlet end of the remediation column was connected to the peristaltic pump by a hose, and the water sample was collected at the water outlet end of the remediation column. After the remediation column was loaded, the remediation column was pre-saturated. After the remediation column is saturated, water is introduced upward from the lower end of the remediation column at a simulated groundwater flow rate; the contaminated groundwater reserve solution ([SMX] = 10 mg / L and [sodium persulfate] = 2 mmol / L) is injected into the dynamic remediation column at a flow rate of 0.44 mL / L for 155 hours to complete the removal of pollutants;
[0081] Sampling was performed at time intervals and the SMX concentration in the samples was detected by HPLC to identify the repair performance of the dynamic repair column; the repair performance was as follows: Figure 4 As shown. In the repair columns filled with 20, 40 and 60 mg of Fe7S8@BC composite repair agent, the reaction time for complete removal of SMX increased to about 30 min, 30 min and 40 min, respectively. With the increase of Fe7S8@BC dosage, the effect of the repair column on removing SMX was enhanced synchronously. After 10 hours, the removal rates of SMX by the repair column were 45.8%, 51.4% and 54.5%, respectively.
[0082] Comparative Example 3
[0083] See also Figure 3 As shown in the left figure, this comparative example provides a dynamic repair column, including a water inlet, a water outlet and a chromatography column;
[0084] The chromatography column is provided with a first filling area, a second filling area and a third filling area, the first filling area, the second filling area and the third filling area are separated by a nylon mesh, the first filling area and the third filling area are filled with glass beads, and the second filling area is filled with quartz sand;
[0085] The water inlet is arranged at one end of the chromatography column and connected to the peristaltic pump to input the contaminated groundwater into the dynamic remediation column;
[0086] The water outlet is arranged at the other end of the chromatography column.
[0087] Contaminated groundwater contains 8-12 mg / L of antibiotics and 1.8-2.2 mmol / L of persulfate.
[0088] Place the reaction column vertically, and fill the remediation column with glass beads (1g, 3.0mm in diameter), quartz sand (quartz sand dosage is 15.02g) and glass beads (1g, 3.0mm in diameter) in sequence. The quartz sand and glass beads are separated by a 100-mesh nylon mesh, and the quartz sand particle size is 1-2mm; then, connect the contaminated groundwater storage bottle to the peristaltic pump through a hose, and then connect the water inlet end of the remediation column to the peristaltic pump through a hose, and collect water samples at the water outlet end of the remediation column; after the remediation column is filled, pre-saturate the remediation column. After the remediation column is saturated, water is introduced upward from the lower end of the remediation column at a simulated groundwater flow rate; inject the contaminated groundwater reserve solution ([SMX] = 10mg / L and [sodium persulfate] = 2mmol / L) into the dynamic remediation column, and inject it at a flow rate of 0.44mL / L for 155h to complete the removal of pollutants;
[0089] Samples were taken at time intervals and the SMX concentration in the samples was detected using HPLC to identify the repair performance of the dynamic repair column; after 10 hours, the removal rate of SMX by the repair column was 9.4%.
[0090] Figure 5 An exemplary application of a biochar-loaded pyrrhotite composite remediation agent in the remediation of groundwater antibiotic contamination is provided. Specifically, the Fe7S8@BC composite remediation agent is injected into different soil layers through injection wells, and the composite remediation agent is continuously injected into adjacent positions in this area to form two rows of parallel agent layers, thereby constructing a reaction zone of the composite remediation agent. Water and sodium persulfate are continuously circulated and injected into the soil layer of the underground contaminated area using injection wells to form a Fe7S8@BC / sodium persulfate advanced oxidation system, which continuously releases strong oxidizing species and efficiently oxidizes and degrades SMX in the soil and groundwater. The water after oxidative degradation is extracted using extraction wells, and the water that meets the discharge standards is again introduced into the injection wells on both sides to form a hydraulic cycle, making the treatment process more economical and efficient.
[0091] Although the principles of the present invention are described in detail above in conjunction with the preferred embodiments of the present invention, those skilled in the art should understand that the above embodiments are merely explanations of the exemplary implementations of the present invention, and are not intended to limit the scope of the present invention. The details in the embodiments do not constitute limitations on the scope of the present invention, and any obvious changes such as equivalent transformations, simple replacements, etc. based on the technical solution of the present invention, without departing from the spirit and scope of the present invention, fall within the protection scope of the present invention.
Claims
1. A method for preparing a composite repair agent of biochar loaded with pyrrhotite, characterized in that: The following steps are involved: S1: After crushing, pyrolyzing, cooling, grinding and screening the carbon-based biomass, BC materials are obtained; S2: Dissolve the iron salt, ferrous salt, sulfur source and BC material, stir evenly, heat, cool to room temperature, wash and dry to obtain a composite repair agent; In the composite repair agent, the molar ratio of Fe7S8 to BC is 1:1-5.
2. The method for preparing the composite repairing agent of biochar loaded with pyrrhotite according to claim 1, characterized in that: In step S1, the pyrolysis method includes the following steps: The crushed carbon-based biomass is heated to 100°C at a rate of 5°C / min at room temperature, maintained for 1 hour, and then heated to 500°C at a rate of 10°C / min, maintained for 2 hours; and / or, The carbon-based biomass is selected from one or more of peanut shells, corn stalks or cow dung; and / or, When pyrolysis is performed, it is carried out under an atmosphere of protective gas, and the protective gas includes one or more of nitrogen, helium or neon.
3. The method for preparing the composite repairing agent of biochar loaded with pyrrhotite according to claim 1, characterized in that: In step S2, the dissolving solvent is one of ethylene glycol and water; and / or, The heating temperature is 220-260° C. and the heating time is 10-14 hours; and / or, The washing solution is pure water and ethanol, and the number of times is at least 3 times; and / or, The drying temperature is 50-70°C and the drying time is 5-7h; and / or, The iron salt is selected from one or more of ferric chloride, ferric nitrate or ferric sulfate; and / or, The ferrous salt is selected from one or more of ferrous sulfate, ferrous chloride or ferrous nitrate; and / or, The sulfur source is selected from one or more of sodium sulfide, thiourea, thioacetamide or elemental sulfur.
4. A composite repair agent of biochar loaded with pyrrhotite, characterized in that: The method is prepared by using the method described in any one of claims 1 to 3.
5. A method for repairing antibiotic contamination of groundwater, characterized in that: The following steps are involved: Adding the composite repair agent of biochar loaded with pyrrhotite and persulfate as claimed in claim 4 to contaminated groundwater containing antibiotics, adjusting the pH value to 2-6 and then shaking; Wherein, the molar ratio of the composite repair agent of biochar loaded with pyrrhotite to persulfate is 1:3.264-13.
056.
6. The method for repairing antibiotic contamination of groundwater according to claim 5, characterized in that: Before pH adjustment, the contaminated groundwater contains 1.5-2.5 mmol / L of a composite remediation agent of biochar-loaded pyrrhotite, 0.3-0.5 g / L of persulfate and 8-12 mg / L of antibiotics; and / or, The persulfate is selected from one or more of sodium persulfate, potassium persulfate or potassium hydrogen persulfate; and / or, The antibiotic is selected from one or more of sulfamethoxazole, ofloxacin or tetracycline.
7. A dynamic repair column, characterized in that: It includes a water inlet, a water outlet and a chromatography column; The chromatography column is provided with a first filling area, a second filling area and a third filling area, the first filling area, the second filling area and the third filling area are separated by a nylon mesh, the first filling area and the third filling area are filled with glass beads, and the second filling area is filled with a mixture of the composite repair agent of biochar loaded with pyrrhotite and quartz sand according to claim 4; The water inlet is arranged at one end of the chromatography column and connected to a peristaltic pump, and is used to input contaminated groundwater into the dynamic remediation column; The water outlet is arranged at the other end of the chromatography column; Wherein, in the second filling area, the mass ratio of the biochar-loaded pyrrhotite composite repair agent to quartz sand is 0.02-0.06:
15.
8. The dynamic repair column according to claim 7, characterized in that: The contaminated groundwater contains 8-12 mg / L of antibiotics and 1.8-2.2 mmol / L of persulfate.
9. Use of the composite repair agent of biochar loaded with pyrrhotite as claimed in claim 4 in repairing antibiotic contamination of groundwater.
10. The use according to claim 9, characterized in that: The application comprises the following steps: The composite repair agent of biochar loaded with pyrrhotite as claimed in claim 4 is injected into different soil layers through injection wells, and the composite repair agent is continuously injected into adjacent positions in this area to form two rows of parallel reagent layers to construct a reaction zone of the composite repair agent; Water and persulfate are continuously circulated and injected into the soil layer of the underground contaminated area through injection wells to form a composite remediation agent / persulfate advanced oxidation system of biochar-loaded pyrrhotite, which continuously releases strong oxidants and efficiently oxidizes and degrades antibiotics in the soil and groundwater; The water after oxidation degradation is extracted through extraction wells, and the water that meets the discharge standards is then introduced into the injection wells on both sides to form a hydraulic cycle.
Citation Information
Cited By
Iron ore modified biochar material as well as preparation method and application thereof
CN121550959A